Optimization of Solid Angle and Count Rate Capability of an X-ray Detector with Backscattering Geometry. Issue 1 (1st December 2022) - Ticchi, G.; Venturelli, M.; Utica, G.; Carminati, M.; Borghi, G.; Zorzi, N.; Falkenberg, G.; Fiorini, C.
Abstract: We study here an optimized geometry for an X-ray detector with hole in the center, as key component for ASCANIO: an innovative 16-channels SDD based spectrometer specifically designed for X-ray fluorescence microscopy (XFM) imaging in synchrotron beamlines. The detector will feature a backscattering geometry with a tilted SDD layout achieving 1 sr solid angle at 8 mm sample distance and a potential Output Count Rate higher than 20 Mcps . The 1 mm thick SDD provides 65 % absorption efficiency at 20 keV while preserving a good energy resolution better than 150 eV thanks to a dedicated cooling system and a low noise front-end electronics. In this paper, the optimization of the detector geometry, in terms of solid angle vs sample distance and maximization of the Output Count Rate introducing a tilting of the SDD units, is discussed.